Kajian Sosial Ekonomi Pelaku Usaha Perikanan Suntung (Loligo Sp) di Kelurahan Makawidey Kecamatan Aertembaga Kota Bitung - Takahipe, Teofianus A.; Durand, Swenekhe S.; Manoppo, Victoria E.N.; Dien, Christian R.; Andaki, Jardie A.; Kotambunan, Olvie V. (AKULTURASI, 2024)
Abstract The purpose of this study is to determine the activities and socio-economic conditions of squid fishermen in Makawidey Village, Aertembaga District, Bitung City. The method used in this study is a survey. A survey is a means of collecting data from sources or research informants by conducting observations and interviews to collect data and research materials. The data collected are primary and secondary data. The results show that the social conditions of squid fishermen include: the age of fishermen in Makawidey Regency is in productive age, fishermen's education is in elementary school with a percentage of 50,000, the condition of the fishermen's house already has a semi-permanent house with a percentage of 100%, the number of family dependents is 1-2 people with the highest percentage of 66.67, the length of time as a fisherman has been more than 30 years with the highest percentage of 50.00%. The economic conditions of squid fishermen are: initial capital of IDR 500,000-IDR 1,000,000 with a percentage of 50.00%, and fishermen's income with an average of IDR 51,840,000 per year, and fishermen's expenditure with an average of IDR 13,566,667 per year. Keywords: socio-economic conditions; squid; Makawidey Abstrak Tujuan dari penelitian ini, yaitu mengetahui aktivitas dan kondisi sosial ekonomi nelayan cumi-cumi di Kelurahan Makawidey Kecamatan Aertembaga Kota Bitung. Metode yang digunakan dalam penelitian ini yaitu survei. Survei adalah sarana mengumpulkan data dari narasumber atau informan penelitian dengan melakukan pengamatan dan wawancara untuk mengumpulkan data dan bahan penelitian.Data yang dikumpulkan berupa data primer dan sekunder Hasil menunjukkan bahwa kondisi sosial nelayan cumi-cumi meliputi: umur nelayan di kabupaten Makawidey berada di usia produktif, pendidikan nelayan pada sekolah dasar dengan presentase 50,000, keadaan rumah nelayan sudah memiliki rumah yang semi permanen dengan presentase 100%, jumlah tanggungan keluarga sebanyak 1-2 orang dengan presentase terbanyak 66,67, lamanya menjadi nelayaan sudah lebih dari 30 tahun dengan presentase terbanyak 50,00%. Kondisi konomi nelayan cumi-cumi yaitu : modal awal Rp500.000- Rp1.000.000 dengan presentase 50,00%, dan pendapatan nelayan dengan rata- rata per tahunnya Rp51.840.000, dan pengeluaran nelayan dengan rata-rata per tahunnya Rp13.566.667. Kata Kunci : Kondisi sosial ekonomi; cumi-cumi; Makawidey